Antibacterial Activity and Mechanism of a Scorpion Venom Peptide Derivative In Vitro and In Vivo - Cao, Luyang; Dai, Chao; Li, Zhongjie; Fan, Zheng; Song, Yu; Wu, Yingliang; Cao, Zhijian; Li, Wenxin (PLOS ONE, 2012)
BmKn2 is an antimicrobial peptide (AMP) characterized from the venom of scorpion Mesobuthus martensii Karsch by our group. In this study, Kn2-7 was derived from BmKn2 to improve the antibacterial activity and decrease hemolytic activity. Kn2-7 showed increased inhibitory activity against both Gram-positive bacteria and Gram-negative bacteria. Moreover, Kn2-7 exhibited higher antibacterial activity against clinical antibiotic-resistant strains such as methicillin-resistant Staphylococcus aureus (MRSA). In addition, the topical use of Kn2-7 effectively protected the skin of mice from infection in an S. aureus mouse skin infection model. Kn2-7 exerted its antibacterial activity via a bactericidal mechanism. Kn2-7 killed S. aureus and E. coli rapidly by binding to the lipoteichoic acid (LTA) in the S. aureus cell wall and the lipopolysaccharides (LPS) in the E. coli cell wall, respectively. Finally, the hemolytic activity of Kn2-7 was significantly decreased, compared to the wild-type peptide BmKn2. Taken together, the Kn2-7 peptide can be developed as a topical therapeutic agent for treating bacterial infections.